Broadening the genetic base of crop production (CABI Publishing, in association with Food and Agriculture Organization of the United Nations and International Plant Genetic Resources Institute, 2001)
This book focuses on the previously neglected interface between the conservation of plant genetic resources and their utilization. Only through utilization can the potential value of conserved genetic resources be realized. However, as this book shows, much conserved germplasm has to be subjected to long-term pre-breeding and genetic enhancement before it can be used in plant breeding programmes. The authors explore the rationale and approaches for such pre-breeding efforts as the basis for broadening the genetic base of crop production. Examples from a range of major food crops (pearl millet, maize, potatoes, cassava and Musa) are presented and issues analysed by leading authorities from around the world. Twenty-seven papers are presented in 4 sections: general principles (7 papers), crop case studies (5 papers), population management (8 papers), and other approaches to broadening the genetic base of crops (7 papers). The book is aimed at plant breeders, genetic resource conservation scientists and research managers in agriculture and biodiversity.